Analisis Faktor yang Berpengaruh terhadap Kualitas Jiwa Kewirausahaan Perajin Stagen Inovasi - Dian Retnaningdiah; Djandjang Purwo Sedjati; Titiana Irawani (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstractThe aim of this research is want to know the effect of creativity and innovation of the entrepreneurship’s quality. The survey methode has been used in this research. The sample number used is 30 respondents from the small medium entrepreneurs with the purposive random sampling technique. The data analysis uses reliability and validity for measuring the questionares. The regression analysis is used as well. By using 5% level of significant, the results show that in partially and simultaneously both creativity and innovation are shown affecting the entrepreneurship’s quality.